2021
DOI: 10.1016/j.heliyon.2021.e06725
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate and crude extracts of Fusarium solani elicit agarwood compounds in shoot culture of Aquilaria malaccensis Lamk.

Abstract: Agarwood forms in the heartwood of trees in the family Thymelaeaceae in response to wounding, infection, or other stresses. Its formation is random and takes decades in natural populations, which are harvested for their aromatic compounds. This harvest has led to declining population, and many agarwood producing trees are considered endangered. Therefore, an alternative source would be desirable. We established an in vitro shoot culture method for one agarwood species, Aquillaria malaccensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Fungal infection typically results in elevated production of free fatty acids, which leads to oxidative bursts, resulting in the production of oxygenated compounds, including jasmonate ( Sen et al., 2017 ), and found that jasmonic acid (JA) can be synthesized by endophytic strains in A. sinensis ( Chen et al., 2017 ). It is widely recognized that JA plays a significant role as a key signaling molecule in triggering the biosynthesis of sesquiterpenes and chromone derivatives in A. sinensis ( Faizal et al., 2021 ). Interestingly, some endophytic fungi in A. sinensis can also synthesis sesquiterpenes, including Acremonium sp., Collectotrichum sp., Fimetariella rabenhorstii , Nigrospora oryzae , and Nodulisporium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infection typically results in elevated production of free fatty acids, which leads to oxidative bursts, resulting in the production of oxygenated compounds, including jasmonate ( Sen et al., 2017 ), and found that jasmonic acid (JA) can be synthesized by endophytic strains in A. sinensis ( Chen et al., 2017 ). It is widely recognized that JA plays a significant role as a key signaling molecule in triggering the biosynthesis of sesquiterpenes and chromone derivatives in A. sinensis ( Faizal et al., 2021 ). Interestingly, some endophytic fungi in A. sinensis can also synthesis sesquiterpenes, including Acremonium sp., Collectotrichum sp., Fimetariella rabenhorstii , Nigrospora oryzae , and Nodulisporium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Use of fungal inoculum is highly prioritized among all type of fungi due to the regular growth of fungal mycelia which continuously spreads in the plant, resulting in wound development and high-yield agarwood formation [16]. Previous study has shown that crude extracts of Fusarium could not lead to the formation or accumulation of sesquiterpenes and 2-2 phenythylchromone in shoot culture of Aquilaria specie plants, whereas methyl jasmonate does [30]. This indicates that the process of agarwood formation…”
Section: Discussionmentioning
confidence: 99%
“…Aquilaria Malaccensis Lam. juga dikenal dengan tanaman kayu gaharu yang merupakan salah satu hasil hutan yang bukan kayu, yangmana pemanfaatan rendemennya diminati oleh industri obat-obatan dan juga di industri kosmetik [5,6,7]. Saat ini, diketahui sangat banyak jenis minyak atsiri yang telah diteliti.…”
Section: Pendahuluanunclassified